Synthesis and optoelectronic properties of a promising quaternary metal oxide light absorber CuBiW2O8. Issue 3 (4th January 2021) - Zhou, Lite; Bainglass, Edan; Masroor, Maryam; Giri, Binod; Li, Guangjiang; Carl, Alexander; Grimm, Ronald L.; Huda, Muhammad N.; Titova, Lyubov V.; Rao, Pratap M.
Abstract : First synthesis of CuBiW2 O8 with direct bandgap of 1.9−2.0 eV and characterization of photoexcited charge dynamics from picoseconds to nanoseconds. Abstract : We have previously predicted CuBiW2 O8 (CBTO) as a novel quaternary metal oxide semiconductor with favorable band gap for applications in photocatalysis and photovoltaics. Here, we report the synthesis of CBTO and the first characterization of its optical, electrical and photoelectrical properties. We demonstrate a Cu-rich solid state synthesis method that enables the synthesis of CBTO powders and continuous thin films. The CBTO contains bulk Bi2 WO6 impurity that is not removed by annealing at higher temperatures, as well as CuO surface impurity. Density Functional Theory (DFT) calculations show that Bi2 WO6 co-exists with CBTO due to reasons of thermodynamic stability and has a type II band offset that may result in electron trapping. CBTO is measured to have a direct band gap of ∼1.9–2.0 eV (which is smaller than existing oxides Cu2 O and BiVO4 ), and optical absorption coefficient of 10 4 to 10 5 cm −1 for visible-wavelength photons. DFT calculations match these results and show that Cu-vacancies are responsible for p-type conductivity, which was also measured by Hall effect. In addition, Hall effect, time-resolved photoluminescence (TRPL), and optical pump – THz probe spectroscopy (OPTP) measurements reveal that both slow hopping transport of trapped carriers (with 0.32 cm 2 V −1 s −1 mobility) over nanosecond timescales and fast band-like motion of free carriers (with ∼150 cm 2 V −1 s −1 mobility) over picosecond timescales result in comparable diffusion lengths of ∼10 nm. However, because this carrier diffusion length is shorter than the optical absorption depth (100–200 nm), nanostructured heterojunctions will likely be needed to achieve efficient solar energy conversion.